Policy Evaluation of Inclusive Education Implementation at SD Negeri Murung Sari 5 Amuntai, Hulu Sungai Utara Regency, South Kalimantan Province - Rina Emilyana; Agus Sukristyanto; Joko Widodo (Jurnal Syntax Admiration, 2024)
In order to provide certainty of educational services for children with physical or mental disabilities or children with special needs in regular education units at PAUD, SD and SMP levels, it is necessary to establish a policy regarding the Implementation of Inclusive Education in North Hulu Sungai Regency in the form of Regent's Regulation No. 40 of the Year 2017 Concerning the Implementation of Inclusive Education in North Hulu Sungai Regency. The CIPP evaluation study used a descriptive qualitative method. Research is qualitative research with a qualitative descriptive model (quasi-qualitative). In this research, informants were also used to obtain comprehensive information about education. The data analysis technique in this research uses descriptive-qualitative analysis techniques, namely carefully abstracting all the information obtained. This means that every data obtained is presented and interpreted in depth and the existing data is analyzed in detail so that it is hoped that adequate conclusions can be obtained. This research resulted in an Evaluation of Policy for Implementing Inclusive education At SD Negeri Murung Sari 5 Amuntai Hulu sungai Utara regency,South Kalimantan selatan, including: Various aspects of the CIPP evaluation concluded that the readiness of schools to implement inclusive education still needs to be improved.